PERAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN DIKLAT (Studi Pada Badan Kepegawaian dan Diklat Kabupaten Pesawaran) - Mustika, Emma; Fatimaningsih, Endry (SOCIOLOGIE, 2013)
The purpose of this study was to determine how the role of the National Employment and Training in motivating the employees to the Employment and Training Agency for discipline in work. What research is Employment and Training Agency Pesawaran District. Source of data obtained through in-depth interviews. The results showed that the role of Personnel and Training Agency in an effort to motivate employees to discipline the work are (1) a program of administrative services, (2) program to improve facilities and infrastructure apparatus, (3) quality improvement program personnel resources, (4) Program coaching and personnel development. The program motivates done as a follow-up to motivate employees to discipline. Factor supporting the existence of sufficient funds from the government and support from local government agencies as well as the desire of the employees own self. Inhibiting factor is the lack of infrastructure, the lack of data from year to year employee.Keywords: Work, motivation, employee, discipline